2016
DOI: 10.1016/j.nmni.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid-resistant mucoid Staphylococcus haemolyticus from a tertiary-care centre in Delhi

Abstract: We report an unusual morphological mucoid variant of Staphylococcus haemolyticus associated with linezolid resistance from a patient with sepsis. Linezolid resistance and mucoid character together made this pathogen difficult to treat. To our knowledge this is the first such report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, one thing different from the study of Luiza et al (2016) is that two (0.9%) MRSH isolates in the present study, on the contrary, showed resistance to vancomycin, the last resort of antibiotic from glycopeptides, posing a threat for the persistence and dissemination of the resistance determinants within healthcare settings. In different studies, it was reported the occurrence of MRSH isolates possessed elevating resistance to glycopeptide antibiotics, such as vancomycin (Veach et al 1990) and teicoplanin (Kristóf et al 2011) as well as linezolid (Chauhan et al 2017;Matlani et al 2016) suggesting the alarming development of MRSH resulting the treatment options to be more limited. Therefore, it is urgently needed to put more attention to the dissemination of the MRSH in the hospital environment through monitoring and surveillance programs so that the risk of infection might be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…However, one thing different from the study of Luiza et al (2016) is that two (0.9%) MRSH isolates in the present study, on the contrary, showed resistance to vancomycin, the last resort of antibiotic from glycopeptides, posing a threat for the persistence and dissemination of the resistance determinants within healthcare settings. In different studies, it was reported the occurrence of MRSH isolates possessed elevating resistance to glycopeptide antibiotics, such as vancomycin (Veach et al 1990) and teicoplanin (Kristóf et al 2011) as well as linezolid (Chauhan et al 2017;Matlani et al 2016) suggesting the alarming development of MRSH resulting the treatment options to be more limited. Therefore, it is urgently needed to put more attention to the dissemination of the MRSH in the hospital environment through monitoring and surveillance programs so that the risk of infection might be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Some S. haemolyticus variants show a mucoid appearance. These mucoid colonies were associated with linezolid-resistant and were difficult to treat [108]. Linezolid-resistant S. haemolyticus isolates were responsible for an outbreak in an Italian intensive care unit [42].…”
Section: Linezolidmentioning
confidence: 99%
“…Species wise susceptibility to linezolid has been reported by various workers; Kalawatet alreported LzRinS. lugdunensisand S.hominis, 6 Peer et al in S.cohnii and S.kloosii, 5 Gupta et alin S.haemolyticus 26 and recently Matlaniet al in 2016 27 reported mucoid strain of S.haemolyticus showingLzR. Such high level of resistance to linezolid is an alarm for the judicious use of this drug.…”
Section: Discussionmentioning
confidence: 93%